Assessment of social competence: exploring the dimensions of young adult social competence - Ang, Chin-Siang (Penerbit Universiti Kebangsaan Malaysia, 2016)
It is very consistent in the sense that social competence was predictive of youth employability. Unlike many previous surveys, the present study utilized multiple measures and provided a more comprehensive picture of social young adults’ perception of social competence in the domains of social (communicative competence and assertiveness), cognition (critical thinking and future orientation), and emotion (identity formation and prosocial tendency). Six measures of social competence were completed by 1134 university students in six randomly selected universities. Analyses revealed most young adults were situationally non-assertive and scored lower communicative competence. Moreover, they were more frequently concerned about family-related, financial-related, and educational-related aspects, but less involved in civic engagement. Of significance, critical thinking or problem-solving skills among young adults should be of concern. The identity formation also poor manifested due to extending exploration of the self and undecided manner in young adulthood. Interestingly, emotional benefits have been directed students to become involved in more prosocial behavior. The findings may be useful for social efforts to promote social competence in early adulthood and for their later working life.